Effects of Dietary Nano-Curcumin Supplementation on Growth Performance, Glucose Metabolism, and Endoplasmic Reticulum Stress in Juvenile Largemouth Bass, Micropterus salmoides - Bao, Xiaoxue; Chen, Mingshi; Yue, Yuhua; Liu, Hua; Yang, Ying; Yu, Hui; Yu, Yingying; Duan, Ning (Frontiers in Marine Science, 2022)
This study evaluated the effects of nano-curcumin on growth performance, mucosal immunity, antioxidant response, glucose metabolism and endoplasmic reticulum stress of largemouth bass. Three groups (three replicates/group) of 270 fish with the mean body weight of 7.00 ± 0.02 g were fed with diets containing 0% (control), 0.1% and 0.2% nano-curcumin for 60 days. The results showed that dietary supplementation of nano-curcumin had no significant effects on the growth performance, body composition, lysozyme (LYZ), alkaline phosphatase (AKP), superoxide dismutase (SOD) and catalase (CAT) activity of largemouth bass. However, dietary supplementation with 0.2% nano-curcumin significantly increased peroxidase (POD) activity in skin mucus and decreased the serum activities of MDA activity compared with the control group. Moreover, dietary supplementation of 0.2% nano-curcumin significantly decreased the levels of blood glucose and liver glycogen, which may be mainly related to the increased gene expression of glucose transporter 2 (GLUT2), glucokinase (GK), phosphofructokinase (PFK), pyruvate kinase (PK). At the same time, the hepatic gene expression of glucose-regulated protein78 (GRP78), activating transcription factor6 (ATF6), inositol-requiring enzyme 1 (IRE) and eukaryotic initiation factor 2α (eIF2α) in 0.2% nano-curcumin group were rapidly suppressed, indicating adding 0.2% nano-curcumin to the diet can alleviate endoplasmic reticulum stress in fish. In conclusion, diets supplemented with 0.2% nano-curcumin effectively improved mucosal immunity, antioxidant properties, glucose metabolism and alleviated ERS induced by long-term carbohydrates intake in largemouth bass.